2009
DOI: 10.1002/cncr.24757
|View full text |Cite
|
Sign up to set email alerts
|

A black‐white comparison of the quality of stage‐specific colon cancer treatment

Abstract: BACKGROUND: Several studies have attributed racial disparities in cancer incidence and mortality to variances in socioeconomic status and health insurance coverage. However, an Institute of Medicine report found that blacks received lower quality care than whites after controlling for health insurance, income, and disease severity. METHODS: To examine the effects of race on colorectal cancer outcomes within a single setting, the authors performed a retrospective cohort study that analyzed the cancer registry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
3
18
1
Order By: Relevance
“…In addition, our analysis indicated an increased risk of death for patients with insurance status other than private insurance among patients who had stage III and high‐risk stage II disease and did not received treatment in adherence to NCCN guidelines (ie, with surgery alone). Similar survival trends relating to insurance status and demographic factors have been noted in several other studies 30‐34…”
Section: Discussionsupporting
confidence: 84%
“…In addition, our analysis indicated an increased risk of death for patients with insurance status other than private insurance among patients who had stage III and high‐risk stage II disease and did not received treatment in adherence to NCCN guidelines (ie, with surgery alone). Similar survival trends relating to insurance status and demographic factors have been noted in several other studies 30‐34…”
Section: Discussionsupporting
confidence: 84%
“…Similar to the current study, their report demonstrated no racial difference in the receipt of oxaliplatin . Because these studies suggest there is no racial disparity in the receipt of chemotherapy, questions remain concerning the reasons why AA patients with CC still have worse outcomes and survival compared with white patients . Although Edwards et al demonstrated that a decline in mortality from colorectal cancer is largely a result of improvements in risk factors and an increased screening rate, Sineshaw et al associated improved survival from CC with access to new treatments …”
Section: Discussionsupporting
confidence: 74%
“…In addition, although non‐CCOP practices may be less likely to provide access to postsurgical evidence‐based adjuvant therapy for stage III CC, AAs treated in CCOPs may be more likely to receive guideline‐concordant treatment . Recognizing and addressing barriers to access are ways to decrease racial disparities in outcomes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach followed the Institute of Medicine's recommendation that central cancer registries be linked to claims and hospital discharge files to provide state or national data on the quality of cancer care [7], and built on the Institute of Medicine's Committee on Assessing Improvements in Cancer Care in Georgia report which translated care quality guidelines into specific metrics that could be applied at the state level [8]. Although other studies have evaluated concordance with guideline therapy for colorectal cancer [6,[9][10][11][12][13][14][15][16][17][18][19], what is unique about this study is its inclusion of the Medicaid population with Medicaid claims data. Quality of care studies indicate that care is inferior for vulnerable populations, including racial and ethnic minorities [20].…”
Section: Introductionmentioning
confidence: 99%